Meningkatkan Hasil Belajar Siswa Kelas XI IPA-1 SMA Negeri 1 Jorong Melalui Pembelajaran Kooperatif Tipe Somatic Auditory Visual And Intellectual Pada Pokok Bahasan Impuls Dan Momentum - Dewantara, Dewi; Jamal, M. Arifuddin (Universitas Lambung Mangkurat, 2013)
The low of studentâs achievements were indicated because the students were not active and the teacherâs lack of skill. This condition needs a further research in order to improve the studentâs achievement through cooperative learning type SAVI in impulse and momentum subject. The specific purposes of this research are to describe: 1) teacherâs skill, 2) the studentâs achievements; 3) the studentsâ participation in the classroom; and 4) the studentsâ responses. These research were classroom action research that consists of 3 cycles. The instruments were used Lesson Plan, Worksheet, Evaluation Sheet, affective scoring sheet, teacherâs skill and studentâs participation observation sheet, and the studentsâ response observation sheet. The data were acquired by the observation results, questionnaire, and documentation. The results of this research were: 1) The teacherâs skill was improved from 99.21% to 96% and 99.28%; 2) the studentsâ achievements including cognitive and affective aspects were improved from 81.46% to 88.1%, and 90.96%; 3) The participation of students in teaching and learning process were also increased from 63.67% to 84.43%, and 85.5% in cycle III, 4) the studentsâ responses during teaching and learning process were very good. According to the results, it can be concluded that the achievements of XI IPA-1 students of SMA Negeri 1 Jorong in learning impulse and momentum were improved after the treatment of cooperative learning model type SAVI.